2021
DOI: 10.1002/hfm.20892
|View full text |Cite
|
Sign up to set email alerts
|

Potential benefits of eye tracking within process control monitoring tasks

Abstract: Statistically, about 70% of the process industry accidents in the refinery control room are caused by human error. It is necessary to develop a deeper understanding of the interaction between humans and the automated systems. This experiment investigated the effectiveness of Overview Displays in a refinery control room by using eye-tracking measures. Specifically, control room operators were presented with three Overview Displays that have been adopted by the oil and gas industry under two levels of difficulty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The relationship between eye-tracking measures and objective SA has been explored for more than a decade and especially in recent years (Argyle, Gourley, Kang, & Shehab, 2020;Desvergez, Winer, Gouyon, & Descoins, 2019;Dini et al, 2017;Liang et al, 2021;Moore & Gugerty, 2010;Salehi et al, 2018;Shi, Noah, Rothrock, & Kim, 2021;Stapel, Hassnaoui, & Happee, 2020;Zhang et al, 2020). For example, Argyle et al (2020) used SAGAT-style probes to investigate the relationship between eye-movement measures and SA in the weather forecasting domain and found a moderate relationship between SAGAT scores and eye-tracking metrics such as total fixation durations and fixation numbers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The relationship between eye-tracking measures and objective SA has been explored for more than a decade and especially in recent years (Argyle, Gourley, Kang, & Shehab, 2020;Desvergez, Winer, Gouyon, & Descoins, 2019;Dini et al, 2017;Liang et al, 2021;Moore & Gugerty, 2010;Salehi et al, 2018;Shi, Noah, Rothrock, & Kim, 2021;Stapel, Hassnaoui, & Happee, 2020;Zhang et al, 2020). For example, Argyle et al (2020) used SAGAT-style probes to investigate the relationship between eye-movement measures and SA in the weather forecasting domain and found a moderate relationship between SAGAT scores and eye-tracking metrics such as total fixation durations and fixation numbers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, fixation duration and fixation numbers have been used in oil refinery studies (Huang et al, 2019;Salehi et al, 2018;Shi et al, 2021). Researchers have shown that number of fixations could be effective and continuous indicators of workload in a control room monitoring task (Huang et al 2019).…”
Section: Visual Behavior Measurements In Oil Refinery Researchmentioning
confidence: 99%
“…Process industries rely on human-automation collaboration to ensure safety. The human operators in the control room monitor the process and intervene when abnormal situations arise ( Shi et al, 2021 ). However, digitalization and the increase in sophistication of automation have altered the operator’s role and introduced additional challenges ( Nazir et al, 2014 ; Di Flumeri et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%